2014
DOI: 10.1055/s-0034-1372509
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neural Response Telemetry and Neural Recovery Function: a Comparative Study between Adults and Children

Abstract: Introduction Neural response telemetry (NRT) is a method of capturing the action potential of the distal portion of the auditory nerve in cochlear implant (CI) users, using the CI itself to elicit and record the answers. In addition, it can also measure the recovery function of the auditory nerve (REC), that is, the refractory properties of the nerve. It is not clear in the literature whether the responses from adults are the same as those from children. Objective To compare the results of NRT and REC between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Carvalho et al revealed no differences between children and adults for NRTs [4]. In this study, an analysis between age and tNRTs showed a tendency of higher values in children less than 1.5 years and users older than 60 years.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Carvalho et al revealed no differences between children and adults for NRTs [4]. In this study, an analysis between age and tNRTs showed a tendency of higher values in children less than 1.5 years and users older than 60 years.…”
Section: Discussionsupporting
confidence: 44%
“…In the literature, NRTs measured intraoperatively are reported to show higher levels than those in the postoperative controls [2]. Further influence factors such as patient's age are discussed contrary [3,4]. The outcome of NRT values also depends substantially on the electrode type as far as length, shape and diameter is concerned [5].…”
Section: Introductionmentioning
confidence: 99%
“…A subgroup analysis of children with connexin mutations did demonstrate a significant association between the comfort level with superior BABY BIO and NU‐CHIPS scores, and a negative correlation with CNC was observed. Although NRT serves as a useful intraoperative tool by providing objective data on auditory nerve responsivity to assess intracochlear placement and help with postoperative programming, 10,14,15 the data do not support NRT responses as being predictive of functional outcomes. Notably, poor electrode responses on NRT do not preclude satisfactory auditory outcomes at a later time point.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear Corporation's NRT utilizes radiofrequency telemetry technology to measure the ECAP of the auditory nerve through the cochlear implant, and the data are analyzed through Cochlear's Custom Sound EP software. An adequate ECAP response is measured by a negative peak with a 0.2 to 0.4 millisecond latency period and typically between 40 and 2000 µV 10 . Demographic, audiometric, treatment and outcome variables were collected from the electronic medical records.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the NRT and the REC, few studies performed evaluations based on the differences between pre and postlingual patients. Carvalho et al 26 compared the values of the NRT in children (aged between 9 months and 11 years) and adults (age range: 18 to 83 years), and showed no difference in the comparison of these two groups except for the saturation level ‘A’ in the basal cochlear region. The patients who were children were mostly prelingual, and the adults were mostly postlingual.…”
Section: Discussionmentioning
confidence: 99%